(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2011)
The issue we propose to analyze is far from having a unanimous solution, although the courts have repeatedly been asked to give their opinion, which should be done as soon as possible, given the high number of lawsuits claiming what those concerned believe to be a real subjective right. The attempt to tackle this challenge aims to provide arguments based on personal reflection, since it has not been possible to verify, to date, an analysis from a similar angle. Unretirement is described by Marisa Ferreira Santos as the deconstruction of the act granting retirement, which depends on the insured person’s expression of will. Its concept presupposes the renunciation of an existing retirement, with a view to using the time spent in contributions or service for a new or better retirement, under the same or a different system. From the outset, it should be noted that a systematic interpretation of the principles and rules that structure the Brazilian legal system would provide legal grounds for adopting the institute, subject, however, to certain conditions in order to reconcile fundamental rights and the survival of the social security framework. In this task, one could not enter the subject without, of course, taking into account the principles, foundations and objectives of the Federative Republic of Brazil enshrined in the Magna Carta from its Preamble onwards, and one cannot fail to take a good look at articles 1 to 3, even in a topographical analysis. It is important to emphasize that the precepts set out in the constitutional text find their genesis and destination in the Preamble to the Federal Constitution, which was extraordinarily capable of condensing legitimate values that become vectors for interpreting the entire Brazilian legal system. As the proposed theme is analyzed, these aforementioned axiological elements must necessarily be taken into account.